Pemanfaatan Sistem Informasi Geografis untuk Lokasi Hotel Guna Mendukung Sektor Pariwisata Kabupaten Jember - Hidayah, Dina Arifah Nur (Jurnal Vokasi Teknik Sipil, 2023)
The geographical location of Jember Regency, which borders the Indian Ocean and Mount Argopuro, makes Jember Regency have potential in the tourism sector. However, there are obstacles in developing the tourism sector in Jember, namely the lack of tourism support such as accommodation. Apart from that, several hotel locations in Jember Regency do not match the coordinates or hotel addresses on Google Maps. This research aims to map hotel locations in the Jember Regency using a Geographic Information System (GIS) and analyze hotel distribution patterns based on location in the Jember Regency. The research method used in this research is a quantitative method with a survey research type. The research results show that the number of hotels has increased to 56 hotels spread across 14 sub-districts, and several hotels are not operating and do not match Google Maps. The results of hotel identification show that 57% of hotels are located on local roads, 56% of hotels are in residential areas, and 62% of hotels can reach tourist attraction. Apart from that, the results of the nearest neighbor analysis show that the hotel distribution pattern is included in the random category.